How Much Is That in Dog Years? The Advent of Canine Population Genomics - BRADLEY, DANIEL (My University, 2014)
ABSTRACT The authors comment on two studies that analyzed multiple genomes of dogs and wolves. The studies reached different conclusions about the date and population effects, a disparity attributed to reliance on molecular evolutionary rates that differ by an order of magnitude. The results of the first study are said to indicate a more complex pattern of amylase copy number variation in dogs and wolves reflecting humans' relationship with dogs, but may not have resulted during early domestication
PUBLISHED
Keywords: Genetics; Dogs; Wolves